Development and research of the model of business structure processes - Левыкин, Виктор Макарович; Халецкая, Ольга Николаевна (Technology audit and production reserves, 2013)
This work is dedicated to development and research of the model of business structure processes. The existing model of the structure of business processes is examined; advantages and disadvantages are selected in an expert way. The main purpose of this study is to develop a more accurate model of the structure of business processes, which can be used in existing information systems for managing business processes. The goal is ensured by resolving the following tasks: study of the existing models used in the creation of the model of the structure of business processes; study of the application of existing models; formation of the performance criteria; development of a combined model. Business Process Management method - one of modern management techniques based on the totality of the ideology and the software business process management - is also examined in the study. The practical significance of the study is in the possibility of application of proposals, recommendations and developments resulting from this study, to optimize business processes of the Internet Technology organizations, which would reduce the costs of obtaining information, time to process it and the quality of data to ensure the success of the organization. Thus, on the basis of expert assessments, a new combined model of the structure of business processes that gives a more accurate assessment is built.